2004
DOI: 10.1088/0031-9155/49/17/001
|View full text |Cite
|
Sign up to set email alerts
|

Variations in dose response with x-ray energy of LiF:Mg,Cu,P thermoluminescence dosimeters: implications for clinical dosimetry

Abstract: In many medical procedures where accurate radiation dose measurements are needed, the variation of detector response with x-ray energy is of concern. The response of LiF:Mg,Cu,P TLDs to a range of x-ray energies was analysed in monoenergetic (synchrotron), diagnostic and therapy radiation beams with the aim of implementing this dosimeter into clinical practice where existing dosimetry techniques are limited due to lack of sensitivity or tissue equivalence (e.g. neonatal radiography, mammography and brachythera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 37 publications
4
56
0
2
Order By: Relevance
“…Nevertheless, both of the related values of dosimeters are placed inside of the trumpet curves. The results are compatible with the energy response of bare dosimeters which have been already reported by other investigators (8,9) .…”
Section: Resultssupporting
confidence: 93%
“…Nevertheless, both of the related values of dosimeters are placed inside of the trumpet curves. The results are compatible with the energy response of bare dosimeters which have been already reported by other investigators (8,9) .…”
Section: Resultssupporting
confidence: 93%
“…Furthermore, while conventional MTS‐N TLDs exhibit an energy response limiting their use in kV dosimetry applications, Duggan et al (18) showed that MCP‐N TLDs are not significantly energy‐dependent at low energies.…”
Section: Methodsmentioning
confidence: 99%
“…TLD‐GR200A (LiF: Mg, Cu, P) (PTW, Freiburg, Germany) circular chips ( 6 ) of dimension 0.8 mm thickness by 4.5 mm diameter were used in this study. The irradiated TLDs were read using a KFKI RMKI TLD reader (KFKI Research Institute of the Hungarian Academy of Sciences, Budapest, Hungary) and were annealed by heating at 240°C for 10 min followed by fast cooling.…”
Section: Methodsmentioning
confidence: 99%